Case Report: Proven Diagnosis of Culture-Negative Chronic Disseminated Candidiasis in a Patient Suffering From Hematological Malignancy: Combined Application of mNGS and CFW Staining - Jin, Yanqi; Wang, Zhouhan; Zhu, Chunxia; Yang, Qing; Lu, Yingfeng; Yu, Xiaopeng; Hong, Bao; Wang, Xiaojing; Zhang, Yimin (Frontiers in Medicine, 2021)
Chronic disseminated candidiasis (CDC) is a severe complication with high morbidity and mortality in patients with hematological malignancies who have undergone chemotherapy. Blood or sterile liver biopsy cultures are negative due to recurrent empirical antifungal therapy. With the escalating resistance to azole-based antifungal drugs in infection by Candida species, pathogen identification is becoming increasingly important for determining definitive diagnosis and treatment strategy. In this case report, we present, for the first time, diagnostic confirmation of a culture-negative CDC case with Candida tropicalis infection using a combination of metagenomics next-generation sequencing and calcofluor white staining.